E-009 A Novel Transvenous Approach to Embolization of an Extensive Transverse and Sigmoid Sinus DAVM in a Patient with an Occluded Ipsilateral Internal Jugular Vein. (29th July 2016) - Adix, M; Choi, I; Kaminsky, I
Abstract : For patients in whom treatment is warranted, dural arteriovenous malformations (DAVMs) can be managed via open surgery, endovascular embolization, or radiation therapy. Endovascular management can be performed from either the arterial or venous side. We describe the case of a patient who presented with left-sided pulsatile tinnitus. Initial cerebral angiogram demonstrated an extensive DAVM of the left transverse and sigmoid sinuses being supplied primarily by branches of the left internal carotid, middle meningeal, and occipital arteries and the right occipital artery. We also observed cortical venous reflux compatible with venous hypertension. Given the extensive arterial supply, a transvenous approach to treatment was chosen. Upon attempted catheterization of the left internal jugular vein (IJ), we discovered that it was occluded up to the level of its junction with the left facial vein. The occluded segment could not be catheterized, so we accessed the patent superior portion of the left IJ via a circuitous route through the left paravertebral plexus. Once the left transverse sinus was successfully catheterized, two major vascular pedicles draining into the transverse sinus and transverse-sigmoid junction were closed with detachable coils in a sinus-sparing procedure. Final angiography demonstrated restoration of anterograde flow through the left transverse and sigmoid sinuses with resolution of the previously seen cortical venous reflux. Only a small residual vascular shunt into the left sigmoid sinus remained. This case demonstrates that patients with DAVMs and ipsilateral IJ obstruction can still be successfully treated via a transvenous approach using alternative venous channels. Disclosures: M. Adix: None. I. Choi: None. I. Kaminsky: None.